Library Administration Office, circa 1918 (1918)
This is believed to be the earliest known photograph of the Cal Poly library. A photo of the 1917 football team published in the June 1917 Polytechnic Journal helps date the photo as after June 1917. Around 1916 the library moved from the Administration building to Science Hall (later named Anderson Hall), second floor.